Educación sexual en jóvenes con discapacidad intelectual del tercer nivel del centro diurno de Desarrollo Integral para Personas con Discapacidad MIES-Loja en el periodo lectivo 2018 - Idrobo Gutiérrez, María Angélica (2018)
Young people with intellectual disabilities have the right to enjoy a free and responsible sexuality. Due to their disability, they behave differently from their chronological age. Through sexual education, young people are trained to avoid risky situations for their physical and mental health, as well as that of others, such as: abuse, pregnancies unwanted and sexually transmitted infections. It is for this reason that the topic of: Sexual Education in Young People with Intellectual Disability of the Third Level of the Integral Development Day Center for Persons with Disabilities MIES-Loja in the 2018 Lecture Period was investigated. For the collection of information, the following was applied: to young people with intellectual disabilities, an observation card, to teachers and parents a survey respectively, this in order to respond to the objectives of the research, which were: Characterize the current state of sex education of the young people with intellectual disabilities, determine if facilitators and parents address issues related to sexuality and develop sex education workshops for young people with intellectual disabilities.